Forgotten and Overlooked: A Personal Reflection of Foster Parenting and School - Seth J Lickteig; Amanda Lickteig (Educational Considerations, 2019)
The number of children in foster care has risen markedly in recent years, namely because of the opioid crisis currently plaguing the United States. Students placed in foster care experience higher dropout and lower graduation rates compared to their peers. School mobility has caused many foster care students to fall through the cracks. However, despite these concerns, teachers and school administrators have received little training regarding this population of students. Schools are ill-prepared for the unique emotional and social needs of children in foster care, often labeling them under the larger umbrella term of at-risk—which focuses primarily on their academic performance. This manuscript serves as a personal reflection by two former middle school teachers as they chronical their experiences with the foster system and schooling. The article posits students in foster care are a unique subgroup of students and identifies four potential areas schools can promote for the exceptional needs of students in foster care.
Keywords: foster care; at-risk students; trauma